PENGARUH PENGGUNAAN MULTIMEDIA CERIA TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN BAHASA INGGRIS DI KELAS III SDN 173209 SIGOTOM - Lestaria Simamora; Dodi F. Pandimun Ambarita; Winara; Syahrial; Masta Marselina Sembiring; Charles Fransiscus Ambarita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the use of cheerful multimedia on student learning outcomes in English learning in grade III of SDN 173209 Sigotom in the 2025/2026 academic year. The research method used is a Pre-Experimental Design with one-group pretest–posttest design. The research sample was taken from all grade III students of SDN 173209 Sigotom using a total sampling technique, as weak as 30 students. The research instrument was an objective test in the form of 20 multiple-choice questions. The results of data analysis showed an increase in the average value of student learning outcomes, namely from 53 in the pretest to 86 in the posttest. The results of the hypothesis test using the Paired Sample T-Test showed a significance value of 0.000 (sig < 0.05), which means that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that there is an effect of the use of cheerful multimedia on student learning outcomes in English learning in grade III of SDN 173209 Sigotom in the 2025/2026 academic year.